Human presence in extreme environments as a condition of knowledge: an Epistemological inquiry - Nielsen, J. N. (Frontiers in Virtual Reality, 2025)
Simulations and immersive technologies have been proposed as alternatives to human presence in isolated, confined or extreme (ICE) environments, but there are limitations to these technologies and techniques that penetrate to the foundations of knowledge. Technologies of simulation and immersion, no matter the fidelity, place a barrier between the knower and the known. While technologies of simulation and immersion should be an integral part of planning and preparation for scientific research in ICE environments, the presence of a human observer in these environments will enter into the construction of any knowledge derived from such environments. Taking space science as a paradigmatic form of research in ICE environments, a conceptual analysis is made of the role of the human observer as a necessary condition of the construction of scientific knowledge.